Effects of finger acupressure combined with lower limb rehabilitation training machine on stroke recovery - Xiaoxue Liu; Feng Zhang; Yanhong Li; Jieqiong Zhao; Yatao Du; Qian Zhang; Weifang Li (Frontiers in Neurology)
BackgroundStroke is a common acute cerebrovascular disease, and rehabilitation therapy plays a crucial role in the recovery of stroke patients.MethodsIn this retrospective study, we first enrolled 80 stroke patients. These participants were then randomly divided into two groups: the treatment group underwent finger acupressure combined with lower limb rehabilitation training machine, and the control group received basic rehabilitation therapy. Baseline differences between the two groups were analyzed, as well as changes in motor function (FMA, sFMA, MAS, 10-Meter Walk Test, 6-Minute Walk Test), balance ability (Tinetti Test, FRT, MRT, TUGT), neural repair markers (NSE, NFL, BDNF), blood and gas exchange parameters (SpO₂, RDW, PLT), and immune and inflammatory responses (CRP, IL-6, IL-10) before and after rehabilitation. A multivariate logistic regression analysis was conducted to evaluate the impact of rehabilitation methods, stroke-related factors, and their interactions on motor function and balance recovery. Additionally, long-term quality of life and one-year recurrence rates were compared between the treatment and control groups.ResultsAfter treatment, compared with the control group, the treatment group showed significant improvements in motor function, balance ability, nerve repair, blood and gas exchange, immune and inflammatory response indicators. In addition to treatment methods, stroke type, stroke location, NIHSS score, and mRS score also significantly affect the recovery of motor function and balance ability. The treatment group has a better therapeutic effect in patients with lower baseline NIHSS scores, mRS scores, and ischemic stroke. The combination of finger acupressure and lower limb rehabilitation training machines can significantly improve the long-term quality of life of patients and reduce the one-year stroke recurrence rate.ConclusionFinger acupressure combined with the lower limb rehabilitation training machine enhances motor function and balance recovery in stroke patients by promoting neural repair, improving immune function, and reducing inflammatory responses. This therapeutic approach is particularly effective in patients with lower baseline NIHSS and mRS scores and those with ischemic stroke.